1984
DOI: 10.1037/0735-7028.15.3.388
|View full text |Cite
|
Sign up to set email alerts
|

Waiting list dropouts in a university counseling center.

Abstract: Waiting List Dropouts in a University Counseling CenterThis study surveys a group of university counseling center clients who were placed on a waiting list and subsequently decided not to renew their request for counseling. The clients (N = 59) who had been on the waiting list during the jail semester were sent a questionnaire asking them to indicate why they did not renew their request for counseling and whether they were still interested. Client responses were analyzed according to type of problem, time on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 6 publications
2
31
0
Order By: Relevance
“…Similar to the findings of previous researchers on waiting list attrition (Anderson et al, 1987;Archer, 1981Archer, , 1984Krauskopf et al, 1981;May, 1990;Obetz et al, 1997), we found that the majority of clients returned to counseling regardless of time on a waiting list. The focus of our study, however, was not simply to determine whether or not the majority of clients returned for services but to examine the characteristics of those clients who did not return.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to the findings of previous researchers on waiting list attrition (Anderson et al, 1987;Archer, 1981Archer, , 1984Krauskopf et al, 1981;May, 1990;Obetz et al, 1997), we found that the majority of clients returned to counseling regardless of time on a waiting list. The focus of our study, however, was not simply to determine whether or not the majority of clients returned for services but to examine the characteristics of those clients who did not return.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, wait-time may interact with certain consumer variables in its impact on attrition. For instance, within the broader mental health literature, some data suggest that pre-intake wait-time may have different effects on attendance based on the urgency of the consumer need (Archer 1984;May 1991). While a clear model of factors contributing to pre-intake attrition in the mental health care of children and adolescents has not yet been empirically identified, there is agreement within the literature that pre-intake attrition is a significant challenge to the efficient delivery of outpatient mental health services.…”
Section: Introductionmentioning
confidence: 97%
“…We expected that increased wait-time would result in increased odds of an unattended appointment. Additionally, based on suggestions in the literature (Archer 1984;May 1991) and clinical intuition, we explored the possible interaction effect between the consumer variable of urgency of need and the clinic variable of wait-time on the prediction of intake attendance.…”
Section: Introductionmentioning
confidence: 99%
“…Many Canadians consider timely access to care as their essential right and a basic pillar of universal health care. 1 Long wait times have been viewed as a threat undermining public confidence in medicare, 2 and have been shown to increase dissatisfaction with care, [3][4][5] as well as morbidity and mortality. 6 Nevertheless, obtaining accurate wait-list data in multicentre research studies is complicated owing to variation in the definitions of wait times and in health record processes.…”
mentioning
confidence: 99%